2001
DOI: 10.1902/jop.2000.72.9.1210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking and Treatment Status on Periodontal Bacteria: Evidence That Smoking Influences Control of Periodontal Bacteria at the Mucosal Surface of the Gingival Crevice

Abstract: Smoking-associated periodontitis is not simply a reflection of oral cleanliness. Smoking extends a favorable habitat for bacteria such as P. gingivalis, P. intermedia, and A. actinomycetemcomitans to shallow sites (< or =5 mm). Molecular byproducts of smoking interfere with mechanisms that normally contain growth of damaging bacteria at the surface of the oral mucosa in gingival crevices. In this way, smoking can promote early development of periodontal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 79 publications
10
61
1
3
Order By: Relevance
“…On the other hand, other studies have not shown a difference between smokers and non-smokers with established periodontal disease (Preber et al 1992, Eggert et al 2001, Salvi et al 2005, Buduneli et al 2005). …”
Section: Tobacco Smoking and Periodontal Microfloramentioning
confidence: 90%
“…On the other hand, other studies have not shown a difference between smokers and non-smokers with established periodontal disease (Preber et al 1992, Eggert et al 2001, Salvi et al 2005, Buduneli et al 2005). …”
Section: Tobacco Smoking and Periodontal Microfloramentioning
confidence: 90%
“…3 In susceptible patients, the clinical effects of smoking are dependent on the number of cigarettes smoked daily and the duration of the habit. 4 The consequences may involve the vascular effect of nicotine 5 and the enhanced production of inflammatory cytokines.…”
Section: N B R I E Fmentioning
confidence: 99%
“…Again, this is in keeping with multiple studies showing that, relative to non-smokers, smokers are more likely to be infected with P. gingivalis, to be infected with higher numbers of this bacterium, and to exhibit more persistent infection by this pathogen (Zambon et al, 1996;Kamma et al, 1999;Eggert et al, 2001;Haffajee & Socransky, 2001). …”
Section: Discussionsupporting
confidence: 83%